IMPROVING STUDENTS’ SPEAKING ABILITY IN RECOUNT TEXT THROUGH PROJECT-BASED LEARNING: A VIDEO PROJECT - Riza Faisma Umim; Armeria Wijaya; list Damayanti (PROCEEDING UMSURABAYA, 2026)
This study aims to investigate the effectiveness of Project-Based Learning (PjBL) through video projects in improving junior high school students’ speaking skills in recount text. Speaking is considered the most challenging English skill due to students’ lack of confidence and fear of making mistakes. To address this, Project-Based Learning was implemented, allowing students to engage in real-world tasks by creating video recordings of their previous experiences. This method was expected to improve students’ speaking skill. The research employed a Classroom Action Research (CAR) design following Kemmis and McTaggart’s model, involving planning, action, observation, and reflection stages. Conducted at a junior high school in Surabaya during the 2024/2025 academic year, the study involved class VIII-E students who initially showed low participation in speaking activities. Data were collected through classroom observations and speaking tests. The result was analyzed using both quantitative and qualitative approaches. The findings were measured by improvements in students’ speaking score after the implementation of project-based learning. The result showed that students speaking ability were improved especially in grammar, pronunciation and structure. In addition, the students were more confident in speaking English after doing and watching their own video because they noticed their mistakes and they were able to correct the mistake. Despite the improvement, the students stated that they needed more speaking activities to enhanced their fluency in speaking English.